Performance Evaluation of the Ge Discovery IQ PET/CT System According to the Nema NU2-2012 Standard - Mia, Md Shohag; Hossain, Md Nahid; Biman, Tanvir Ahmed; Kabir, M F Fazlul (Bangladesh Journal of Physics, 2025)
A PET/CT Scanner -Discovery IQ 5 ring. GE Medical system was installed at Evercare Hospital Dhaka. Total of 11252 BGO crystal elements are arranged in 5 circular rings providing 260 mm axial and 700 mm trans axial field of view. The aim of the test was to assess the performances of the PET/CT scanner GE-Discovery IQ 5 ring. Spatial resolution, Image Quality, and Sensitivity tests were carried out as per NEMA NU2-2012 Standard guidelines. Spatial resolution for radial, tangential and axial directions was carried out at (x,y): (0,1), (0,10), and (0,20) cm locations. Sensitivity was calculated from the activity concentration factor. Image reconstruction algorithm VPHD was used. The radial, tangential, and axial FWHM 4.2 mm, 4.74 mm, and 4.82 mm at 1 cm; 5.72 mm, 4.82 mm, and 4.57 mm at 10 cm off center; 8.17 mm, 4.85 mm, and 4.92 mm at 10 cm off center respectively. In NEMA image quality, the hot contrast recovery values for 10-13-17-22 mm spheres were 25.7- 50.3-56.1-69.7 % respectively and cold contrast recovery values for 28 mm and 37 mm spheres were 75.5 and 77.7 % respectively; the corresponding background variability values were 7.2-6.9-6.6-5.9-5.5-4.7 %. The lung error residual mean was 16 %. Overall, PET performances of the Discovery IQ whole body scanner were satisfactory and passed the entire NEMA NU2- 2012 acceptance test. Bangladesh Journal of Physics, Vol. 30, Issue 2, pp. 57–67, December 2023